Severe vesiculobullous lesions with purpuric macules associated with chikungunya virus (Archives of Pediatrics of Uruguay, 2025)
Introduction: chikungunya fever is a re-emerging viral infection, which presents a great variety of lesions on the skin and mucous membranes. We describe the case of a child with confirmed Chikungunya virus infection who, during his evolution, presented extensive and severe vesiculo-bullous and maculo- purpuric lesions.Clinical Case: a 6-year-old male patient consulted for high fever, generalized maculo-papular rash, and severe arthralgia that made walking difficult. Physical examination revealed a generalized erythematous rash on the chest and abdomen with islands of normal skin, similar to that observed in dengue virus infection, in addition to purpuric and large vesiculo-bullous lesions filled with abundant serous fluid in the upper and lower limbs. Ulcerative lesions such as canker sores on the tongue, and marked palmoplantar desquamation. He received immunoglobulin 400 mg/kg/day for 5 days and methylprednisolone 30 mg/kg single dose, the blisters were debrided. Excellent evolution. Serology: negative Elisa test for Dengue. Chikungunya IgM: positive.Discussion: vesiculo-bullous and purpuric macules are rare and atypical lesions as an unusual manifestation of Chikungunya virus infection, simulating Stevens-Johnson Syndrome-Toxic Epidermal Necrolysis, erythema multiforme, and autoimmune bullous diseases. The classic clinical picture of the disease does not include the observation of these lesions, which constitute a diagnostic challenge. They have been observed in neonates, young infants, and rarely in adults, as well as ulcerative lesions on the tongue such as canker sores and marked palmoplantar desquamation, rarely described in Chikungunya fever.Conclusions: this atypical and severe case suggests the inclusion of Chikungunya in the differential diagnosis of bullous febrile dermatosis.
Keywords: Chikungunya Virus; Chikungunya Fever; Vesiculobullous Skin Diseases